Unbiased enrichment of urine exfoliated cells on nanostructured substrates for sensitive detection of urothelial tumor cells. (10th November 2019) - Wang, Xin; Gu, Yuanyuan; Zhang, Shiwei; Li, Gangqiang; Liu, Tianyao; Wang, Tianwei; Qin, Haixiang; Jiang, Bo; Zhu, Lin; Li, Yajun; Lei, Haozhi; Li, Ming; et al.
Abstract: Background: Early detection of urothelial carcinoma (UC) by noninvasive diagnostic methods with high accuracy is still underscored. This study aimed to develop a noninvasive assay incorporating both enrichment of urine exfoliated cells and immunoassays for UC detection. Methods: Polystyrene dishes were exposed to oxygen plasma and modified with 3‐aminopropyltriethoxysilane to prepare amine‐functionalized nanostructured substrates (NS). Performance characterization of NS was evaluated by atomic force microscope and X‐ray photoelectron spectroscopy. Urine exfoliated cells were captured by NS and then immunostained to detect urinary tumor cells (UTCs), which was called UTC assay. The receiver operating characteristic (ROC) curve, area under ROC curve (AUC), and Youden index were used to find the cutoff value of UTC assay. ROC analysis and McNemar test were used to compare the diagnostic accuracy of UTC assay with cytology. Kappa test was used to analyze the agreement of UTC assay and cytology with pathological diagnosis. Results: Nanostructured substrates had good cell binding yields of nucleated cells and tumor cells. CK20 + CD45 − CD11b − cells were considered as UTCs. UTC number ≥ 1 per sample could be considered as a positive result. By AUC and Kappa analysis, UTC assay showed good performance in UC detection. McNemar test demonstrated that UTC assay had a superior sensitivity even in low‐grade subgroup and a similar specificity compared to cytology in UC diagnosis. Conclusions: Nanostructured substrates could be used to enrich the exfoliated cells from urine samples. UTC assay with NS has the potential to play a role in UC detection. The value of this assay still needs additional validation by large, multi‐center studies. Abstract : Nanostructured Substrates (NS) could be used to enrich exfoliated nucleate cells from urine samples. The assay based on NS enrichment and immunocytology could be a novel non‐invasive diagnostic tool for urothelial carcinoma (UC).